Niche expansion by indigenous fish species following the introduction of rainbow trout (Oncorhynchus mykiss) in a subtropical river system, upper Blyde River, South Africa - Maimela, Lerato T.; Chimimba, Christian T.; Zengeya, Tsungai A. (Frontiers in Environmental Science, 2022)
The introduction of alien predatory fish such as rainbow trout (Oncorhynchus mykiss) can have a significant effect on indigenous fish communities such as altering the structure and dynamics of food webs. Quantifying the trophic niche utilised by the alien fish species is therefore important to aid our understanding of how their feeding strategies might aid establishment, define their functional role and inform on potential impacts. This study assessed food web interactions between fish communities in river reaches that are invaded by O. mykiss and sections that are free of invasions in the upper Blyde River catchment, South Africa. It specifically evaluated the hypothesis that O. mykiss invasion is likely to lead to a decrease in the trophic functional diversity through predation and that indigenous fish will shift their trophic niche to either minimise competition with, or avoid predation, by O. mykiss. Gut content and stable isotope analyses were used to determine trophic interactions. Fish communities in uninvaded areas utilised fewer and similar food sources and occupied lower trophic levels, than fish communities in invaded areas. Oncorhynchus mykiss fed mainly on invertebrates and at trophic levels similar to and or lower than indigenous fishes. This suggests that their current impact on indigenous fish communities is mainly through competition for resources. We posit that O. mykiss invasions reduced the abundance of indigenous fishes and thereby reduced predation pressure on aquatic invertebrates, with a knock-on effect on the trophic interrelationships among fish assemblages. Our findings are consistent with other studies in South Africa that have shown that the impacts of O. mykiss invasion can lead to a decline and fragmentation of indigenous species populations and niche shifts.